El impacto de la familia en el proceso de enseñanza-aprendizaje, en los niños y niñas del sexto año de educación básica de la Escuela IV Centenario N° 1 de la Ciudad de Loja y la intervención del trabajador social - Morocho Nero, Tania Maria (2016)
The family is the natural and fundamental group unit of society and is entitled to protection by society and the State Family is a group of people united by love, understanding and tolerance. Its members have emotional or kinship ties. Some are formed by parents and children. But others include grandparents, uncles, cousins and others close. This research aims to contribute to the understanding of the problems investigated on the limited commitment of the family and its influence on the process of teaching and learning of children / as and transform relations between children (as) - family environment in family spaces and education, by generating meeting places where children involved, and teachers are familiar environment. All this in order to positively influence a better accompaniment of parents in the education of their children an impact on school performance and strengthening the links between the parties. The objectives in this research allowed the causes and consequences taking into account the data collected children under study against their families and their participation in the process of teaching and learning, and then propose alternatives that go to strengthen the appropriate commitment of parents through the intervention of the social worker. findings that determine the causes of the problem investigated were found to be a limiting factor demonstrating the limited involvement of parents in the school because for lack of time; the work does not allow them to help your child with homework and teachers report that when they attend the institution is only because they require and not on their own to learn about the needs of children